Sustainable Fashion and Textile Recycling - de la Motte, Hanna; Ostlund, Asa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The clothing and textile industry is a resource-intensive industry and accounts for 3 to 10 percent of global carbon dioxide emissions. In addition, the industry is extremely linear and generates large amounts of waste. For the industry to move from a linear to a circular economy, several solutions are required along the value chain: upstream by working with resource efficiency, the longevity of textile products, and preventing waste; and downstream with techniques for sorting and recycling. In addition, solutions for traceability and transparency need to be developed and coordinated as accepted methods for sustainability measurements. This Special Issue (SI) "Sustainable Fashion and Textile Recycling" brings together areas of knowledge along the textile value chain to highlight the difficulties and opportunities that exist from both a broader perspective and in specific issues. In this SI, these 11 papers are mainly devoted to new research in traceability, design, textile production, and recycling. Each valuable article included in this Special Issue contributes fundamental knowledge for a transformation of the textile and fashion industry to take place. Numerous studies, solutions, and ideas need to be carried out to create the innovations that will become the reality of our future. Likewise, we need to learn from each other and take advantage of all the fantastic knowledge that is generated globally every day towards a better future for generations to come.